THE IMPACT OF CULTURAL DAKWAH ON EDUCATION AND ISLAMIZATION: A Case Study at “Desa Santri”, Kajen, Pati - Ravida Chauria Shavir (Ath Thariq Jurnal Dakwah dan Komunikasi, 2021)
Syaikh Ahmad Mutamakkin is a well-known advocate of Islamic conversion and dissemination in Java, particularly in the Pati area. He lived in the 17th century, during the reign of the great Sultan of Mataram. According to the study, cultural preaching has a connection to the development of “Santri Village” in Kajen, Pati. This qualitative study employs a case study and employs observation, interview, and documentation techniques. The study revealed the development of the “Desa Santri,” which is a counterculture and alternative values among communities, with its original value and culture development manifesting itself in three forms: local wisdom, education, and Islamization. Furthermore, the study reveals how Shaykh Mutamakkin's messages were accepted in communities where Islam was still in the minority at the time.